Design, Optimization and Implementation of a High Frequency Link Multilevel Cascaded Inverter - Hasan, Md. Mubashwar (Curtin University, 2018)
This thesis presents a new concept of cascaded MLI (CMLI) device reduction by utilizing low and high frequency transformer link. Two CMLI topologies, symmetric and asymmetric are proposed. Compared with counterpart CMLI topologies available in the literatures, the proposed two inverter topologies in this thesis have the advantages of utilizing least number of electronic components without compromising overall performance particularly when a high number of levels is required in the output voltage waveform.